PENGEMBANGAN BAHAN AJAR TARIKH ISLAM UNTUK SISWA KELAS VIII SMP MUHAMMADIYAH BOARDING SCHOOL YOGYAKARTA - Yumidiana Tya Nugraheni (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
The unavailability of Islamic history teaching materials in accordance with the principles of teaching materials and curriculum of the Muhammadiyah Boarding School of Yogyakarta is a background that encourages writers to research, develop and test the feasibility of Islamic history teaching materials for students in class VIII of Muhammadiyah Boarding School of Yogyakarta. This reseach aims to determine, develop and test the appropriateness of Islamic history teaching materials used for students of class VIII at Muhammadiyah Boarding School of Yogyakarta. This research uses qualitative and quantitative approaches to the type of research and development. Data collection techniques in this research used the method of observation, interviews, and questionnaires. The test subjects in this research were Islamic history’s teachers and VIII grade students of Muhammadiyah Boarding School of Yogyakarta. The results of this research produced a product in the form of Islamic history teaching materials for students of class VIII of Muhammadiyah Boarding School of Yogyakarta entitled“al-Tarikh al-Islami (fi Sirah Rasulillah Shallallah ‘alaihi wa Sallam).” After the validation test from the expert, from the aspects of appearance, presentation and learning got results with very good categories. Based on the results of teacher and student responses from aspects, content and material got results with the category of